Anti‐inflammatory effects of the petasin phyto drug Ze339 are mediated by inhibition of the STAT pathway. (31st January 2017) - Steiert, Sabrina A.; Zissler, Ulrich M.; Chaker, Adam M.; Esser‐von‐Bieren, Julia; Dittlein, Daniela; Guerth, Ferdinand; Jakwerth, Constanze A.; Piontek, Guido; Zahner, Catherine; Drewe, Juergen; Traidl‐Hoffmann, Claudia; Schmidt‐Weber, Carsten B.; et al.
Abstract : Ze339, an herbal extract from Petasites hybridus leaves is effective in treatment of allergic rhinitis by inhibition of a local production of IL‐8 and eicosanoid LTB4 in allergen‐challenged patients. However, the mechanism of action and anti‐inflammatory potential in virally induced exacerbation of the upper airways is unknown. This study investigates the anti‐inflammatory mechanisms of Ze339 on primary human nasal epithelial cells (HNECs) upon viral, bacterial and pro‐inflammatory triggers. To investigate the influence of viral and bacterial infections on the airways, HNECs were stimulated with viral mimics, bacterial toll‐like‐receptor (TLR)‐ligands or cytokines, in presence or absence of Ze339. The study uncovers Ze339 modulated changes in pro‐inflammatory mediators and decreased neutrophil chemotaxis as well as a reduction of the nuclear translocation and phosphorylation of STAT molecules. Taken together, this study suggests that phyto drug Ze339 specifically targets STAT‐signalling pathways in HNECs and has high potential as a broad anti‐inflammatory drug that exceeds current indication. © 2016 BioFactors, 43(3):388–399, 2017